2023
DOI: 10.1088/1755-1315/1252/1/012079
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Adding with Organic Nutrient (Complex-Groop) and Spraying with Kinetin on Some Characteristics of Vegetative Growth and Yield of Pomegranate Trees Punica granatum L. Cv. Salimi

M F Al-Doori,
S A Hussein

Abstract: The study was conducted in a private orchard in Owainat region in Tikrit city of Salah al-Din Governorate - Iraq, during the growing season 2022. To study the effect of adding the organic nutrient Complex-Groop at three concentrations (0, 125, 250) g Tree−1 in two batches, the first on 2/15 and the second on 5/15 – 2022, and spraying with growth regulator of Kinetin at three concentrations (0, 75, 150) ml L−1 with three sprays during the growing season, where the first spray was on 3/15, the second on 4/15, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 11 publications
2
2
0
Order By: Relevance
“…The addition of humic acid to the soil leads to an increase in the absorption of nutrients, an increase in the strength of the growth of the root group, and its improvement as a result of an increase in dry and wet weight, an increase in the lateral branches of the roots, in addition to an increase in the plant content of proteins. And its role is similar to the role of auxins in increasing cell division, which encourages plant growth [24] This agrees with the results reached [25][26][27]. It is worth noting that humic acid dissolves in water easily and is easy to add, and its effectiveness is fast and leaves no harmful effects on humans or the environment [28], and these results are consistent with what was indicated in a study on apple trees of the Anna variety, where [29] found that spraying with humic acid at a concentration of 5% led to a significant increase in the average weight of the fruit, reaching 152.46 g., relative to the treatment The comparison that gave 120.54 g. [30] noted in their study on apricot trees, cultivar Labib -1 , that the ground addition of humic acid at a concentration of 6 g.L -1 led to an increase in the yield of one tree, reaching 16.957 kg.…”
Section: Discussionsupporting
confidence: 89%
“…The addition of humic acid to the soil leads to an increase in the absorption of nutrients, an increase in the strength of the growth of the root group, and its improvement as a result of an increase in dry and wet weight, an increase in the lateral branches of the roots, in addition to an increase in the plant content of proteins. And its role is similar to the role of auxins in increasing cell division, which encourages plant growth [24] This agrees with the results reached [25][26][27]. It is worth noting that humic acid dissolves in water easily and is easy to add, and its effectiveness is fast and leaves no harmful effects on humans or the environment [28], and these results are consistent with what was indicated in a study on apple trees of the Anna variety, where [29] found that spraying with humic acid at a concentration of 5% led to a significant increase in the average weight of the fruit, reaching 152.46 g., relative to the treatment The comparison that gave 120.54 g. [30] noted in their study on apricot trees, cultivar Labib -1 , that the ground addition of humic acid at a concentration of 6 g.L -1 led to an increase in the yield of one tree, reaching 16.957 kg.…”
Section: Discussionsupporting
confidence: 89%
“…When it evaporates, the level of elements in the leaves increases [9] which is reflected in an increase in the content of the leaves and stems of macronutrients and carbohydrates. These results are consistent with [25][26][27]. The Kamali variety outperformed the Halwani variety in terms of phosphorus in the leaves, potassium in the leaves, carbohydrates in the leaves, nitrogen in the cuttings, phosphorus in the cuttings, potassium in the cuttings, and carbohydrates in the cuttings Table (3,4,5,6,7,8,9) This is a genetic trait related to the variety and the genes responsible for those traits [28] while the Halwani variety was significantly superior to Al-Kamali in terms of nitrogen in the leaves Tables (3) This is attributed to the genetic variation of the studied varieties and their behavior in distributing different parts of the vine.…”
Section: Carbohydrates In the Cuttings (%)supporting
confidence: 91%
“…Nitrogen plays an important role in many of the vital processes that occur in the plant, such as the formation of amino acids, proteins and enzymes, which encourage cell divisions and cell elongation, which is reflected in an increase in the rate of plant height, leaf area and number of leaves (Emongor and Emongor, 2023) [6] . Its role increases the number and size of leaf cells and the formation of chlorophyll, which leads to an increase in the effectiveness of the leaves in photosynthesis and thus increase vegetative growth (Popov, 1978 and Al-Doori and Hussein, 2023) [18,2] .…”
Section: -mentioning
confidence: 99%
“…the spraying with a salicylic growth regulator has been affected significantly if the concentration of 150 mg liter -1 exceeds the rest of the concentrations and amounted to 95.03 cm 2 compared with the comparison treatment, which rose to 73.91 cm 2 , and as for the effect of the varieties, the Kamali variety significantly outperformed the Halwani variety because of its values at 99.42 cm 2 . The interaction between the levels of coverage and the varieties had a significant effect on this trait, as the coverage with charcoal for the Kamali variety was significantly superior to the rest of the interactions and amounted to 102.66 cm 2 . As for the bilateral interaction between the levels of spraying with the salicylic growth regulator and the varieties, spraying with a concentration of 150 mg L -1 of salicylic for the Kamali variety was significantly superior to the rest of the interactions at 109.59 cm 2 .…”
mentioning
confidence: 99%